Spirituality as a Philosophical Category - Tukhtarov I. (Genius Journals, 2022)
The article deals with the epistemological issues related to the philosophical meaning of the category of spirituality, its importance in social cognition. Different approaches to the problems of the formation of spiritual being, its role in the life and development of society are analyzed
Keywords: Society; spirituality; morality; humanity